IMPLEMENTASI PERATURAN DAERAH KABUPATEN KARIMUN NOMOR 15 TAHUN 2010 TENTANG KEGIATAN PERTAMBANGAN (STUDI KASUS PERTAMBANGAN GRANIT OLEH PT KAWASAN DINAMIKA HARMONITAMA TAHUN 2012 - Yandri Pratama; Muhammad Ridwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The research present describe the implementation of district regulation Karimun Regency Number 15, 2010 about mine resources (study case by Kawasan Dinamika Harmonitama Comapany in Karimun Regency). Karimun Regency one of Regency that has potency in granite, but until now this potency still needed controlling by government in manage of mines activity in Karimun Regency.The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Karimun Regency and researcher collect data from books, government regulation, jurnal, mass media, website and deep interview with informan likes Karimun Head of Regency, Mines and Mineral Agency, staff Kawasan Dinamika Harmonitama Company and Sememal society in Meral District Karimun Regency.The conclution of this research are implementation of district regulation Karimun Regency Number 15, 2010 about mine activity by Kawasan Dinamika Harmonitama Regency are not effective. Its cause by some factor, are: communication actor between Karimun Regency government with Kawasan Dinamika Harmonitama Company, minim of quality and quantity by staff in Mines Mineral and Energy Agency of Karimun Regency, unwilingness factor from company to receive the protest from society about blasting activity of granite stones and also bureaucration structure of government that only Head of Regency has a authority to stopped the mine activity of Kawasan Dinamika Harmonita Company.Keywords: Implementation, District Regulation, and Mines.